Effects of ionizing radiation on bio-active plant extracts useful for preventing oxidative damages. Issue 8 (18th April 2019) - Mulinacci, Nadia; Valletta, Alessio; Pasqualetti, Valentina; Innocenti, Marzia; Giuliani, Camilla; Bellumori, Maria; De Angelis, Giulia; Carnevale, Alessia; Locato, Vittoria; Di Venanzio, Cristina; De Gara, Laura; Pasqua, Gabriella
Abstract: Humans are exposed to ionizing radiations in medical radiodiagnosis and radiotherapy that cause oxidative damages and degenerative diseases. Airplane pilots, and even more astronauts, are exposed to a variety of potentially harmful factors, including cosmic radiations. Among the phytochemicals, phenols are particularly efficient in countering the oxidative stress. In the present study, different extracts obtained from plant food, plant by-products and dietary supplements, have been compared for their antioxidant properties before and after irradiation of 140 cGy, a dose absorbed during a hypothetical stay of three years in the space. All the dry extracts, characterized in terms of vitamin C and phenolic content, remained chemically unaltered and maintained their antioxidant capability after irradiation. Our results suggest the potential use of these extracts as nutraceuticals to protect humans from oxidative damages, even when these extracts must be stored in an environment exposed to cosmic radiations as in a space station. Abstract :